The Community-Based Restoration Monitoring System (CBRMS): A guide to using CBRMS in peatland restoration monitoring - Okarda, B.; Basuki, I.; Baral, H. (Center for International Forestry Research, 2023)
Monitoring is a crucial element of any peatland ecosystem restoration process, and well-designed monitoring programmes can improve the effectiveness of restoration efforts. Monitoring can measure progress toward restoration goals, and further improve the efficacy of the restoration process itself. Monitoring an ongoing project can also directly enhance restoration outcomes and improve future restoration decision making. Restoration monitoring does pose challenges and frequently faces constraints, including limited funds and human resources. Internet of Things (IoT)-based monitoring systems are available for doing so, but their coverage is limited, and they are unable to show restoration impacts on a local scale. Accordingly, we developed the Community-Based Restoration Monitoring System (CBRMS). This CIFOR-ICRAF flagship product offers the capacity to work offline, is compatible with more affordable smartphones, allows safe storage on cloud systems, is transparent and accessible, and facilitates local community involvement. It is designed as an organized system for collecting, processing and validating data necessary for measuring implementation progress and impacts, while empowering communities to participate in monitoring processes. The mobile application is designed to be user friendly and reliable, and offers high flexibility for modification to suit user requirements. This book outlines the monitoring system framework and provides guidelines for its application. We hope it can help practitioners and facilitators in monitoring progress made in restoration efforts on the ground.